Synthesis and characterization of natural sensitizers for dye sensitized solar cells - Kimpa, Mohammed Isah; Uthman Isah, Kasim; Yabagi, Jibrin Alhaji; Taufiq, Sulaiman; Agam, Mohd Arif (Path of Science, 2017)
Natural dyes of anthocyanin extract from flame tree flower (Delonix regia) and chlorophyll extract from pawpaw leaf (Carica papaya) were used as sensitizer to fabricate dye sensitized solar cell (DSSC). The photoelectrode were subjected to UV/Vis spectrophotometer to view their absorbability. The photo electrochemical performances of DSSCs obtained from I.V characteristics showed conversion efficiency, (ɳ) of 0.80 % for the dye extracts from flame tree flower (anthocyanine), with open-circuit voltage (VOC) of 0.5249 mV, short-circuit current density (Isc) of 44.6191 mA/m2 and Fill factor (FF) of 0.5837. Chlorophyll dyes extract from pawpaw leaf has VOC, Isc, FF and conversion efficiency, (ɳ) of 0.5249 mV, 16.5283 mA/m2, 0.5585 and 0.27 % respectively. The conversion efficiency for the mixed dyes (anthocyanin and chlorophyll) at ratio 1:2 is 0.23 % with VOC, Isc and FF of 0.5500 mV, 14.2750 mA/m2 and 0.5451 respectively, while the dye mixture at ratio 1:4 achieved VOC of 0.5249 mV, Isc of 18.4941 mA/m2, FF of 0.5206 and conversion efficiency (ɳ) of 0.26 %. Anthocyanine from flame tree flower dye extract had the higher conversion efficiency of 0.8 % which could be better in term of application in dye solar cell.